Intraspecific chromosome polymorphisms can lead to reproductive isolation and speciation: an example in red brocket deer (Mazama americana) - Salviano, Mauricio Barbosa; Cursino, Marina Suzuki [UNESP]; Zanetti, Eveline dos Santos [UNESP]; Abril, Vanessa Veltrini; Barbanti Duarte, Jose Mauricio [UNESP] (Oxford Univ Press Inc, 2017)
The red brocket (Mazama americana) is a South American deer with a wide geographical distribution that presents different chromosomal variants depending on their location. At least six different cytotypes belonging to two distinct evolutionary lineages have been described. This study aimed to verify the existence of postzygotic reproductive isolation between cytotypes of M. americana by comparative evaluation of pure and hybrid males. Seven 18-month-old bucks were submitted to seminal collection and evaluation and testicle histological evaluations. The pure males showed normal parameters for sperm quality and testicular histology. Hybrids from the same evolutionary lineage (<= 3 chromosomes different from the progenitors) showed similar results to pure males, except for the reduced ratio of round spermatids to pachytene spermatocytes. Hybrids between cytotypes of different evolutionary lineages (>= 10 chromosomes different from progenitors) presented azoospermia and evidence of testicular degeneration. Despite the striking morphological similarities, we can conclude that populations with more distinct karyotypes possess an effective reproductive barrier; moreover, there is evidence that reproductive isolation mechanisms exist between some closer karyotypes, corroborating the hypothesis that M. americana is best characterized as a superspecies. Thus, the future description of several new species for this taxon is expected, since the tendency is to establish efficient mechanisms of postzygotic reproductive isolation, preventing the introgression and fusion of genomes from different populations through chromosome variation. Summary Sentence Differences equal to or greater than seven chromosomes produce an effective reproductive isolation between red brocket deer cytotypes and a depression in fertility occurs among karyotypes with at least two chromosome diferences.
Keywords: cervidae; genetics; chromosomes; evolution; meiosis; fertility